Security implications of nationalism in Eastern Europe - Simon, Jeffrey, 1942-; Gilberg, Trond, 1940- (ROUTLEDGE, 2019)
Suggesting that events in Poland during 1980-1981 represent the tip of an iceberg, the contributors examine the rise of nationalism in Eastern Europe and its potential consequences for European security. They analyze developing problems and trends in the region, including the cooling of relations between the USSR and individual countries in Eastern Europe, the continuing economic crisis, changing social structures, the influence of the intelligentsia, and the eroding importance of ideology as a key part of Eastern Europe's political culture. The second half of the book focuses on the impact of these shifts on political and military relations between the USSR and Eastern European countries and on the efficient functioning of the Warsaw Pact.
Keywords: National security -- Europe, Eastern -- Congresses.; Communist countries -- Congresses.; Nationalism -- Europe, Eastern -- History -- 20th century -- Congresses.; Pays socialistes -- Congrès.; Nationalisme -- Europe de l'Est -- Histoire -- 20e siècle -- Congrès.; HISTORY -- General.; National security; Nationalism; Communist countries; Eastern Europe; Kommunismus; Nationalismus; Sicherheitspolitik; Wirtschaftsentwicklung; Ostblock; Osteuropa; 1900-1999; Conference papers and proceedings; History; Kongress.